Cryptomenorrhea due to Agenesis of Upper Part of Vagina Treated by Vaginoplasty with Amnion Graft and Cervicovaginal Anastomosis: a Case Report (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Cryptomenorrhea due to vaginal agenesis is a rare developmental anomaly of Mullerian duct. It may be complicated by retrograde menstruation, endometriosis and acute or chronic pelvic infection. We report a case of a 12-year-old girl who presented with a history of severe cyclical lower abdominal pain for 2 months. Her clinical examination revealed well developed secondary sexual characteristics, slightly bulged lower abdomen with a palpable tender mass and a short blind vagina. Ultrasound imaging showed hematometra, hematocervix and vaginal agenesis. She was treated by vaginoplasty with amnion graft and cervicovaginal anastomosis with serial vaginal dilatation using plastic vaginal mold. The patient was symptom free with regular menstruation on follow up visit at 1, 3 and 9 months. The Uterus was normal in size with empty cavity and well-defined endometrial lining on ultrasound.Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):49-51